Wireless LAN/FM radio-based robust mobile indoor positioning: an initial outcome - Wan Bejuri, Wan Mohd. Yaakob (2014)
The location determination in an obstructed area can be extremely challenging especially if the Global Positioning System (GPS) is blocked. In such conditions, users will find it difficult to navigate directly on-site, especially within an indoor environment. Occasionally, this needs to integrate with other sensors in order to determine the location with greater intelligence, reliability and ubiquity. In this paper, we will utilise the function of a mobile sensing platform (MSP) by integrating a wireless local area network (WLAN) and FM radio. These positioning sensors will be switched based on the user's environment in order to ensure the robustness of the indoor positioning system. Finally, we will present our preliminary results to illustrate the performance of the system for an indoor environment set-up.